KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SINTANG DALAM PEMBERIAN PELAYANAN AKTA KELAHIRAN - Debby Biliemia Noviandrie E.42009029 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This essay writing  is intended to study and analyze employee performance effectiveness of Population and Civil Registration office Sintang regency and to identify and analyze employee performane productivity of Population and Civil Registration office Sintang regency in birth certificate service. The title of this essay was appointed to examine the effectiveness and productivity of employee performance in achieving organizational golas in birth certificate service in Sintang regency. This research uses descriptive qualitative research. The research was used by four research steps, namely a preliminary investigation (presurvey), field operation, processing and analysis of data and report research (skripsi). The study site is in the Population and Civil Registration office Sintang regency. the subject research are the Head of Population and Civil Registration  office Sintang regency, Head of Civil Registration, crew of civil registration and Citizens birth certificate maker. The Results of this study show that the effectiveness of employee performance is still not optimal, such as still going incorrect in typing the name on the birth certificate and the employees who lack knowledge in work,  and then  the productivity performance of the employee is still not optimal too, as can be seen from not achieving the targets of Population and Civil Registration office Sintang regency  and the work produced unsatisfactory employees regarding birth certificates. This can be seen clearly from compliance workload and perceived use has not been enough time to finish all the work in the field of Civil Registration. the limited number of employees and the lack of facilities and infrastructure owned can be obstacle in completing the work. Keywords: Employee Performance, Effectiveness, Productivity